Supercritical CO2 dyeing for nylon, acrylic, polyester, and casein buttons and their optimum dyeing conditions by design of experiments. (October 2019) - Bai, Tierong; Kobayashi, Kota; Tamura, Kazuhiro; Jun, Yan; Zheng, Laijiu
Graphical abstract: Highlights: We designed and developed a compact scCO2 dyeing apparatus for plastic buttons. Plastic buttons of nylon, acrylic, polyester, and casein were dyed in scCO2 . From the Taguchi method, we found an optimum K/S value for dyeing plastic buttons. Color difference ΔE* of plastic buttons dyed was evaluated by CIE L*a*b* theory. Abstract: Supercritical carbon dioxide (scCO2 ) dyeing for textile and polymer processing is considered as a green and energy-saving process for view-points of environmental friendly and sustainable development. We developed a compact scCO2 dyeing apparatus and performed scCO2 dyeing for plastic buttons of nylon, acryl, polyester, and casein with a uniformly color at the temperature T, pressure P, and dyeing time t. The dye sorption in the buttons was examined by the dyeing color depth, which was evaluated by K/S values calculated from Kubelka-Munk equation. From the range analysis and variance analysis based on the Taguchi design of experiments, we found an optimum dyeing condition of K/S values for dyeing plastic buttons at T = 125 ℃, P = 27 MPa, and t = 80 min for nylon, T = 50 ℃, P = 14 MPa, and t = 40 min for acrylic, T = 120 ℃, P = 12 MPa, and t = 30 min for polyester, and T = 80 ℃, P = 10 MPa, and t = 30 min for casein, as well as the most influential factor and rank of influence factors for all plastic resin buttons. In addition, the color difference ΔE* of plastic buttons of nylon, acrylic, polyester, and casein dyed at the optimum operation conditions was evaluated by CIE L*a*b* theory.